N FORMULASI DAN UJI KARAKTERISTIK GEL JERAWAT EKSTRAK ETANOL KUNYIT (Curcuma domestica Val.) : Formulation and Characterization of Turmeric (Curcuma domestica Val.) Ethanol Extract Acne Gel - Novan Visia Farmasari; Dyah Rahmasari; Binti Maulidia; Dian Ermawati (LPPM Universitas Abdurrab, 2025)
Acne vulgaris is a common skin problem often caused by genetic, hormonal, dietary, psychological factors, climate, P. acnes bacterial infection, and cosmetic use (Sampelan et al., 2013). Gel preparations are chosen for their cooling effect, ease of spreading, and easy washability. Turmeric (Curcuma domestica Val.), a tropical plant originating from Southeast Asia, has long been utilized as a preventive and curative agent for various diseases, including its potential antibacterial properties. This study aimed to determine the effect of varying concentrations of turmeric extract (5%, 7.5%, and 10%) on the physicochemical characteristics and stability of gel preparations using the freeze-thaw cycling method. Turmeric extract was prepared by maceration using 96% ethanol solvent. The gel formula contained CMC-Na as a base, citrate buffer, propylene glycol, glycerin, PEG 400, Na EDTA, TiO2, and aquadest. The gel preparations were evaluated for physical characteristics (organoleptic, homogeneity, viscosity, flow type, spreadability) and chemical characteristics (pH), as well as their stability. The evaluation results showed that variations in turmeric extract concentration significantly affected the organoleptic properties (color change), viscosity, spreadability, and pH of the preparations. Although all formulas were homogeneous, the freeze-thaw cycling stability test revealed that Formula I (5%) was physically unstable (phase separation) and experienced a significant decrease in pH (p<0.005), indicating the instability of the turmeric gel preparation due to temperature influence. However, all preparations remained homogeneous and their pH stayed within the safe range for skin. Thus, this study confirms the significant influence of turmeric extract concentration on the characteristics and stability of the gel, with higher concentrations (7.5% and 10%) showing better physical stability.